2011
DOI: 10.3109/09537104.2011.632031
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume and Platelet Distribution Width in non-diabetic subjects with Obstructive Sleep Apnoea Syndrome: New indices of severity?

Abstract: MPV and PDW are higher in non-diabetic patients with severe OSAS and are correlated with different parameters of breathing function during sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 39 publications
3
111
0
6
Order By: Relevance
“…We think that is directly related between PDW and improvement of oxygenation. Several previous studies have demonstrated a direct correlation between AHI level and PDW values (10,11). This improvement in PDW values with CPAP treatment is a quite reasonable result.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We think that is directly related between PDW and improvement of oxygenation. Several previous studies have demonstrated a direct correlation between AHI level and PDW values (10,11). This improvement in PDW values with CPAP treatment is a quite reasonable result.…”
Section: Discussionsupporting
confidence: 72%
“…Mortality in patients disusing CPAP is higher than those using (9). Previous studies have demonstrated that disease severity and hypoxia are correlated with MPV and PDW in OSA (10). Another study demonstrated that PDW values were increased but MPV values were not changed in severe OSA (11).…”
Section: Introductionmentioning
confidence: 92%
“…Recently, Wasilewski et al have reported that all‐cause mortality is 1.5‐fold higher in non‐ST‐segment elevation myocardial infarction patients with high MPV values 17. In earlier studies, MPV and PDW were found to be significantly higher in patients with severe OSA when compared with control subjects 23, 24. In this study, we firstly found that MPV and platelet large cell ratio values of ACS patients taking DAPT with moderate/severe OSA were significantly higher than those without, and that MPV correlated with AHI, oxygen desaturation index, and minimum SaO 2 (%) (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 94%
“…These studies were hypothesized that the alterations in MPV may be a confounding factor behind the increased cardiovascular events in OSA (4,6,7,23). One another platelet indices, PDW, was also reported to be higher in non-diabetic patients with severe OSA when compared to control group (5,9). Another study by Kurt et al reported a meaningful correlation between PDW and AHI (17).…”
Section: Discussionmentioning
confidence: 98%
“…During routine complete blood count analyze, mean platelet volume (MPV) and platelet distribution width (PDW) are the most commonly measured platelet indices. In earlier studies, MPV and PDW were found to be significantly higher in patients with severe obstructive sleep apnea (OSA) when compared to control subjects (4)(5)(6)(7)(8)(9). MPV was also reported to be correlated with disease severity and inflammation in patients with obstructive sleep apnea and therefore, it could be used as a marker to predict cardiovascular diseases in patients with OSA (6)(7)(8).…”
Section: Introductionmentioning
confidence: 97%